1988
DOI: 10.1093/infdis/158.6.1268
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Neutrophil Function in Patients With AIDS or AIDS-Related Complex: A Comprehensive Evaluation

Abstract: We measured the neutrophil function of 6 patients with AIDS and Kaposi's sarcoma (KS); 22 patients with AIDS-related complex (ARC); and 28 healthy, heterosexual controls. Neutrophils from patients with ARC showed significantly less chemotaxis (P less than or equal to .025) than did those from patients with AIDS and KS or from controls. Serum from patients with AIDS and KS or with ARC significantly (P less than or equal to .05) inhibited chemotaxis of neutrophils from controls; heat treatment of the serum aboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
2
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(87 citation statements)
references
References 25 publications
5
78
2
2
Order By: Relevance
“…It is possible that this unresponsiveness is a re¯ection of stunted development of the immune system in perinatally HIV-infected children. In fact, the absence of any increase in the MFI of the newly expressed CD64 in the paediatric HIV patients' PMNs and the complete absence of any responses in the expression of other immunologically important receptors CD16, CD32 and CD11b throughout all classes of perinatal HIV infection in this study clearly differ from the ®ndings reported in studies on adult ARC [9,11]. In our view, these differences strongly favour the possibility of a stunting effect of the perinatally transmitted HIV infection on the development of the immune system.…”
Section: Fluorescent Staining Of Pmnscontrasting
confidence: 92%
“…It is possible that this unresponsiveness is a re¯ection of stunted development of the immune system in perinatally HIV-infected children. In fact, the absence of any increase in the MFI of the newly expressed CD64 in the paediatric HIV patients' PMNs and the complete absence of any responses in the expression of other immunologically important receptors CD16, CD32 and CD11b throughout all classes of perinatal HIV infection in this study clearly differ from the ®ndings reported in studies on adult ARC [9,11]. In our view, these differences strongly favour the possibility of a stunting effect of the perinatally transmitted HIV infection on the development of the immune system.…”
Section: Fluorescent Staining Of Pmnscontrasting
confidence: 92%
“…gp41 has been detected in brain tissues of patients affected by AIDS dementia (22) and Abs recognizing various epitopes of gp41 appear at early stages of HIV infection (61). Moreover, it has been reported that monocytes and neutrophils from HIV-1-infected patients responded poorly to a variety of chemoattractants, including FMLP (62)(63)(64)(65)(66). The interaction of gp41 peptides with FPRs on human basophils might be of clinical relevance in patients with HIV-1 infection.…”
Section: Increasing Evidence Indicates That Human Fc⑀rimentioning
confidence: 99%
“…Although B cell abnormalities are recognized [2], neutrophil dysfunction is also well described [3]. Published data on neutrophil function in HIV infection are difficult to interpret, as results are inconsistent and often conflicting due to differences in method, in study populations and in concomitant medication [3][4][5][6][7]. Abnormal neutrophil chemotaxis is the most commonly described defect for most HIV þ groups.…”
Section: Introductionmentioning
confidence: 99%